2012
DOI: 10.1123/jsm.26.3.237
|View full text |Cite
|
Sign up to set email alerts
|

Recurring Sport Events and Destination Image Perceptions: Impact on Active Sport Tourist Behavioral Intentions and Place Attachment

Abstract: Hosting recurring sport events can be a solution for sustainable tourism development resulting in destination loyalty and higher place attachment levels. This study proposes active event sport tourists may include in their destination perceptions a number of destination and event attributes, given the direct association of the event with the place. The feasibility of the convergence of event and destination image attributes in one scale was explored and that scale’s influence on place attachment and on specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
1
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(134 citation statements)
references
References 57 publications
6
111
1
16
Order By: Relevance
“…This study aims at providing a consumer-based approach to investigate the role of the event and the place not through its tangible features [10] but rather through the eyes of attendees, as the personal connection individuals feel with the event and the place. Also perceived value has been suggested as a relevant predictor of revisiting [1,8,9], and prior study has indicated that providing events is a major task of a touristic destination [35]. Many studies reported that it influences visitors' revisit intentions [3,5,6].…”
Section: Conceptual Model and Hypothesesmentioning
confidence: 99%
“…This study aims at providing a consumer-based approach to investigate the role of the event and the place not through its tangible features [10] but rather through the eyes of attendees, as the personal connection individuals feel with the event and the place. Also perceived value has been suggested as a relevant predictor of revisiting [1,8,9], and prior study has indicated that providing events is a major task of a touristic destination [35]. Many studies reported that it influences visitors' revisit intentions [3,5,6].…”
Section: Conceptual Model and Hypothesesmentioning
confidence: 99%
“…With regard to the relationship between destination image and destination loyalty, Kaplanidou, Jordan, Funk, and Ridinger (2012) investigated the effect of destination image of sport tourists on place attachment and behavior intention. They found that the more positive the destination image, the higher the behavior intention.…”
Section: Destination Loyaltymentioning
confidence: 99%
“…Generally speaking, past findings confirm that destination image is a critical factor leading to place attachment. Kaplanidou, Jordan, Funk, and Ridinger [55] investigated the impact of destination image factors on behavioral intention and place attachment in terms of sporting events and affirmed that attractions, destination atmosphere, and the event characteristics of the destination's image predicted place identity and dependence. Lee, Busser, and Yang [56] examined a conceptual model describing the relationships among these predictors that create the destination image, the actual image itself, and place attachment, arguing that cognitive image and affective image were direct antecedents of all place attachment dimensions.…”
Section: Place Attachmentmentioning
confidence: 98%